Endometriosis and cardiovascular disease. Issue 1 (2nd February 2022) - Marchandot, Benjamin; Curtiaud, Anais; Matsushita, Kensuke; Trimaille, Antonin; Host, Aline; Faller, Emilie; Garbin, Olivier; Akladios, Chérif; Jesel, Laurence; Morel, Olivier
Abstract: Endometriosis is a chronic gynaecological disease affecting 1 in 10 reproductive-age women. It is defined as the presence of endometrium-like tissue outside the uterus. Beyond this placid anatomical definition, endometriosis is a complex, hormonal, inflammatory, and systemic condition that poses significant familial, psychological, and economic burden. The interaction between the cardiovascular system and endometriosis has become a field of interest as the underlying mutual mechanisms become better understood. On the basis of accumulating fundamental and clinical evidence, it is likely that there exists a close relationship between endometriosis and the cardiovascular system. Therefore, investigating the endometriosis—cardiovascular interaction is highly clinically significant. In this review, we highlight our current understanding of the pathophysiology of endometriosis with systemic hormonal, pro-inflammatory, pro-angiogenic, immunologic, and genetic processes beyond the peritoneal microenvironment. Additionally, we provide current clinical evidence about how endometriosis interacts with cardiovascular risk factors and cardiovascular disease (CVD). To date, only small associations between endometriosis and CVD have been reported in observational studies, inherently limited by the potential influence of unmeasured confounding. Cardiovascular disease in women with endometriosis remains understudied, under-recognized, and underdiagnosed. More detailed study of the cardiovascular-endometriosis interaction is needed to fully understand its clinical relevance, underlying pathophysiology, possible means of early diagnosis and prevention. Graphical Abstract: